2018
DOI: 10.1007/s00535-017-1425-z
|View full text |Cite
|
Sign up to set email alerts
|

Mac-2 binding protein glycan isomer (M2BPGi) is a new serum biomarker for assessing liver fibrosis: more than a biomarker of liver fibrosis

Abstract: Assessing liver fibrosis is important for predicting the efficacy of antiviral therapy and patient prognosis. Liver biopsy is the gold standard for diagnosing liver fibrosis, despite its invasiveness and problematic diagnostic accuracy. Although noninvasive techniques to assess liver fibrosis are becoming important, reliable serum surrogate markers are not available. A glycoproteomics study aimed at identifying such markers discovered Mac 2-Binding Protein Gylcan Isomer (M2BPGi), which is a reliable marker for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
158
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(164 citation statements)
references
References 71 publications
4
158
1
1
Order By: Relevance
“…In addition to the liver stiffness value measured by FibroScan and AST‐to‐platelet ratio, several studies focused on other noninvasive methods for evaluating liver fibrosis in the CHB population, such as the fibrosis index based on 4 factors (age, platelet count, ALT, and AST) and the Forn index (a formula based on the platelet count, γ‐glutamyl transferase, age, and cholesterol). Both of them can detect liver fibrosis successfully .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the liver stiffness value measured by FibroScan and AST‐to‐platelet ratio, several studies focused on other noninvasive methods for evaluating liver fibrosis in the CHB population, such as the fibrosis index based on 4 factors (age, platelet count, ALT, and AST) and the Forn index (a formula based on the platelet count, γ‐glutamyl transferase, age, and cholesterol). Both of them can detect liver fibrosis successfully .…”
Section: Discussionmentioning
confidence: 99%
“…M2BP is a glycoprotein produced by hepatic stellate cells and is present in small amount in many tissues in human body, including the extracellular matrix in the liver. It is extensively glycosylated, that is, becomes M2BPGi, and interacts with galectin‐3 (Mac‐2) and other extracellular matrix molecules and functions as a messenger between hepatic stellate cells and Kupffer cells for promotion of fibrogenesis . Therefore, it has been studied as a surrogate marker of liver fibrosis in various liver diseases including viral hepatitis .…”
Section: Introductionmentioning
confidence: 99%
“…It is extensively glycosylated, that is, becomes M2BPGi, and interacts with galectin-3 (Mac-2) and other extracellular matrix molecules and functions as a messenger between hepatic stellate cells and Kupffer cells for promotion of fibrogenesis. 16 Therefore, it has been studied as a surrogate marker of liver fibrosis in various liver diseases including viral hepatitis. [17][18][19][20][21] A recent paper reported that a high serum M2BPGi at 48 weeks of antiviral therapy predicted HCC development in 234 CHB patients during 51 months of follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…M2BP is widely expressed in various human tissues, but a liver‐specific glycosylation isomer (M2BPGi) can be determined and quantified using the Wisteria floribunda agglutinin immunoassay that is already commercially available in Japan . In the recent years, M2BPGi has emerged as a novel biomarker that correlates well with hepatic fibrosis in patients with chronic liver diseases . Recent literature also suggests that M2BPGi may correlate with hepatocellular carcinoma (HCC) development in patients with chronic viral hepatitis, but most have been conducted in patients with chronic hepatitis C (CHC) or untreated chronic hepatitis B (CHB) without serial measurements …”
Section: Introductionmentioning
confidence: 99%
“…2 In the recent years, M2BPGi has emerged as a novel biomarker that correlates well with hepatic fibrosis in patients with chronic liver diseases. 3 Recent literature also suggests that M2BPGi may correlate with hepatocellular carcinoma (HCC) development in patients with chronic viral hepatitis, but most have been conducted in patients with chronic hepatitis C (CHC) or untreated chronic hepatitis B (CHB) without serial measurements. [4][5][6][7][8] Indeed, the serum concentration of M2BPGi is not static and may change in a relatively short period of time, especially in the setting of anti-viral therapies.…”
Section: Introductionmentioning
confidence: 99%